2008
DOI: 10.1128/aac.00853-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antibacterial Activities of DC-159a, a New Fluoroquinolone

Abstract: DC-159a is a new 8-methoxy fluoroquinolone that possesses a broad spectrum of antibacterial activity, with extended activity against gram-positive pathogens, especially streptococci and staphylococci from patients with community-acquired infections. DC-159a showed activity against Streptococcus spp. (MIC 90 , 0.12 g/ml) and inhibited the growth of 90% of levofloxacin-intermediate and -resistant strains at 1 g/ml. The MIC 90 s of DC-159a against Staphylococcus spp. were 0.5 g/ml or less. Against quinolone-and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 25 publications
(25 reference statements)
3
30
0
Order By: Relevance
“…DC-159a showed the lowest MICs and the narrowest MIC distribution against M. tuberculosis and NTM isolates for the tested drugs. A good activity of DC-159a against quinoloneresistant strains in other bacteria has been reported previously (2,7). The results of this study also confirmed the characteristic advantage of DC-159a against QR-MDR M. tuberculosis.…”
supporting
confidence: 79%
“…DC-159a showed the lowest MICs and the narrowest MIC distribution against M. tuberculosis and NTM isolates for the tested drugs. A good activity of DC-159a against quinoloneresistant strains in other bacteria has been reported previously (2,7). The results of this study also confirmed the characteristic advantage of DC-159a against QR-MDR M. tuberculosis.…”
supporting
confidence: 79%
“…Similarly, new orally active compounds in the class that retain activity against staphylococci that exhibit resistance to current fluoroquinolone agents could potentially expand the range of options for the management of MRSA and MRSE infections in the community setting. To date, medicinal chemistry efforts have yielded a series of novel 4-quinolone class agents that exhibit in vitro activities against ciprofloxacin-resistant pneumococci and staphylococci, including delafloxacin (ABT-492) (2), garenoxacin (3,25,32), DC-159a (9,29,31), and WCK-771 (5, 6). However, no members of the 4-quinolone class are currently approved for use for the treatment of infections mediated by MRSA or fluoroquinoloneresistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In contemporary surveillance studies of health care-associated MRSA isolates, the rate of ciprofloxacin resistance is routinely reported to be Ն50%, and currently approved fluoroquinolones are indicated for use only for the treatment of staphylococcal infections mediated by methicillin-susceptible strains. However, a series of investigational fluoroquinolones have been reported to exhibit good in vitro activities against MRSA, including ciprofloxacin-resistant strains (2,5,25,29,45), and several of these agents are reported to be undergoing clinical evaluation for the treatment of complicated skin and skin structure infections (cSSSIs), including infections caused by MRSA strains.…”
mentioning
confidence: 99%
“…This agent has been shown previously to have potent in vitro activity against other bacterial pathogens causing diseases in the respiratory tract, including Streptococcus pneumoniae, S. pyogenes, S. agalactiae, Haemophilus influenzae, H. parainfluenzae, Moraxella catarrhalis, and Bordetella pertussis (5,6). The only susceptibility data available for DC-159a thus far are those in a report providing MICs for 10 strains of M. pneumoniae (4). The present study was undertaken to investigate the comparative in vitro inhibitory and bactericidal activities of DC-159a against a collection of mycoplasma and ureaplasma species that are known to cause disease in humans.…”
Section: Mycoplasmal Species Of Human Origin Including Mycoplasma Pnmentioning
confidence: 99%